The relationship of symptom dimensions with premorbid adjustment and cognitive characteristics at first episode psychosis: Findings from the EU-GEI study - Ferraro, Laura; La Cascia, Caterina; La Barbera, Daniele; Sánchez-Gutiérrez, Teresa; Tripoli, Giada; Seminerio, Fabio; Sartorio, Crocettarachele; Sideli, Lucia; Arango, Celso; Arrojo, Manuel; Bernardo, Miguel; Bobes, Julio; et al. (Elsevier B.V., 2022)
Premorbid functioning and cognitive measures may reflect gradients of developmental impairment across diagnostic categories in psychosis. In this study, we sought to examine the associations of current cognition and premorbid adjustment with symptom dimensions in a large first episode psychosis (FEP) sample. We used data from the international EU-GEI study. Bifactor modelling of the Operational Criteria in Studies of Psychotic Illness (OPCRIT) ratings provided general and specific symptom dimension scores. Premorbid Adjustment Scale estimated premorbid social (PSF) and academic adjustment (PAF), and WAIS-brief version measured IQ. A MANCOVA model examined the relationship between symptom dimensions and PSF, PAF, and IQ, having age, sex, country, self-ascribed ethnicity and frequency of cannabis use as confounders. In 785 patients, better PSF was associated with fewer negative (B = −0.12, 95% C.I. −0.18, −0.06, p < 0.001) and depressive (B = −0.09, 95% C.I. −0.15, −0.03, p = 0.032), and more manic (B = 0.07, 95% C.I. 0.01, 0.14, p = 0.023) symptoms. Patients with a lower IQ presented with slightly more negative and positive, and fewer manic, symptoms. Secondary analysis on IQ subdomains revealed associations between better perceptual reasoning and fewer negative (B = −0.09, 95% C.I. −0.17, −0.01, p = 0.023) and more manic (B = 0.10, 95% C.I. 0.02, 0.18, p = 0.014) symptoms. Fewer positive symptoms were associated with better processing speed (B = −0.12, 95% C.I. −0.02, −0.004, p = 0.003) and working memory (B = −0.10, 95% C.I. −0.18, −0.01, p = 0.024). These findings suggest that the negative and manic symptom dimensions may serve as clinical proxies of different neurodevelopmental predisposition in psychosis.
Keywords: cognitive domains; first episode psychosis; IQ; premorbid adjustment; symptom dimensions; transdiagnostic; Scopus; JCR